Amino Acid Composition of Some New Varieties of Leguminous Seeds - Saxena, Priya; Shrivastava, S.K.; Saxena, P. (Asian Journal of Chemistry, 2010)
Six new varieties of leguminous seeds, i.e., Pisum sativum variety Arkel and JM-1, Cicer arietinum variety Phule G81-1-1 Vijay, DTT RII BG-391 and JG-7 and Lens esculenta variety JL-1 were analyzed for their amino acid composition by high performance liquid chromatography.